A Novel Mutation in the NCF2 Gene in a CGD Patient With Chronic Recurrent Pneumopathy - de Albuquerque, Jose Antonio Tavares; Lima, Alessandra Miramontes; de Oliveira Junior, Edgar Borges; Ishizuka, Edson Kiyotaka; Aragão-Filho, Walmir Cutrim; Bengala Zurro, Nuria; Mayumi Chiba, Sônia; Fernandes, Fátima Rodrigues; Condino-Neto, Antonio (Frontiers in Pediatrics, 2019)
Chronic granulomatous disease (CGD) is an inherited, genetically heterogeneous disease characterized by defective phagocytic cell microbicidal function, leading to increased susceptibility to bacterial and fungal infections. CGD is caused by mutations in components of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase system, which is responsible for reactive oxygen species production during phagocytosis. Mutations in the neutrophil cytosolic factor 2 (NCF2) gene account for <5% of all cases. Here, we report a case of a 2-year-old female with persistent recurrent pneumopathy, even under trimethoprim-sulfamethoxazole (TMP-SMX) and itraconazole prophylaxis combined with IFNγ treatment. Genetic analysis revealed a novel mutation in NCF2, sequence depletion in a splicing region (c.256_257+2delAAGT NM_000433), leading to a K86Ifs*2 residue change in the p67-phox protein.